Mentoring of the MSME Communication Forum in Tirtoadi Village, Mlati, Sleman Towards Digital Transformation - Unan Yusmaniar Oktiawati; Victor Ilen Segara; Haris Aditya Mandala; Darline Lanek; Sabiha Zahratunnada; Ratu Salma Bani Ismail; Maximillian Hanzel Dias Putra; Sela Nurhayati; Vanya Shauqia Marsha; Dinda Farica Anaz; Cahaya Putra Kurnia Wijaya; Intan Aprilia Arlisti; et al. (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The Tirtoadi UMKM Communication Forum (Forkom) plays a crucial role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Kalurahan Tirtoadi. However, this organization faces various internal challenges, such as inefficient human resource management, and external challenges, such as limited access to digital markets. This mentoring activity is one of the community service programs in collaboration with the Student Work Program (KKN) of Universitas Gadjah Mada, aimed at testing the effectiveness of implementing a computerized Human Resource Information System (HRIS) in addressing internal challenges and digital transformation in improving the competitiveness of MSMEs at the local level. Through surveys and in-depth interviews, this activity found that HRIS can improve the efficiency of managing member data and organizational activities. Meanwhile, digital transformation is expected to expand market access and increase MSME revenue. The results of this activity are expected to provide policy recommendations for village governments and relevant organizations in supporting the development of digital-based MSMEs.